2006
DOI: 10.1007/s00702-005-0430-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus-response compatibility in Parkinson’s disease: a psychophysiological analysis

Abstract: The present study investigated the mechanisms underlying stimulus-response compatibility effects in Parkinson's disease patients and matched controls. Since basal ganglia are involved in the selection and inhibition of competing responses we examined whether basal ganglia dysfunction in Parkinson's disease leads to greater interference effects compared to the control subjects. Reaction times and lateralized movement-related cortical potentials (lateralized readiness potential: LRP) were recorded in two modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 33 publications
5
50
1
Order By: Relevance
“…The increased attentional processing affects subsequent processing stages of action selection. Data from the e-LRP, reflecting automatic response activation (Falkenstein et al 2006), show a stronger activation of the incorrect response hand on flanker presentation of the AA/AG genotype group. Hence the existence of an A allele seems to adversely affect action selection as driven by the flankers.…”
Section: Attentional Processing and Action Selectionmentioning
confidence: 87%
See 2 more Smart Citations
“…The increased attentional processing affects subsequent processing stages of action selection. Data from the e-LRP, reflecting automatic response activation (Falkenstein et al 2006), show a stronger activation of the incorrect response hand on flanker presentation of the AA/AG genotype group. Hence the existence of an A allele seems to adversely affect action selection as driven by the flankers.…”
Section: Attentional Processing and Action Selectionmentioning
confidence: 87%
“…The stimulus-locked (s-LRP) waveforms in incongruent, conflicting trials in a Flanker task usually show an early activation of the incorrect response hand ("dip") (Beste et al 2008a). This dip precedes the negative deflection that reflects the correct response activation may be strongly driven by stimulus processing (Falkenstein et al 2006). TNF-␣ exerts neuroprotective effects in occipital brain structures.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The third clue was provided by clinical investigations showing that PD patients are generally found to be dysfunctional on measures of response inhibition [21], supporting the view that executive control over responses is compromised in PD [22,23]. However, inconsistent observations are reported regarding the nature of this broad deficit: While some authors found that PD patients have difficulties inhibiting an ongoing reaction [22,24,25], others suggested an enhancement instead of an impairment of inhibitory control [26]. We assume that these inconsistencies are partly due to the fact that current models of inhibitory control of responses, and derived psychophysical methods, are incomplete and unable to evidence important executive mechanisms ignored so far.…”
Section: From the Motor To The Executive Hypothesismentioning
confidence: 94%
“…In PD, several studies found enhanced interference effects (e.g. Praamstra and Plat, 2001;Praamstra et al, 1998;Wylie et al, 2005), but see Falkenstein et al (2006). However, in these studies patients with a long history of PD were examined, being either under medication or tested after a short time period off-medication.…”
Section: Introductionmentioning
confidence: 99%